(untitled) (مجلة المنصور, 2022)
A numerical three dimensional investigation is performed to study the effects of the heat flux and Reynolds number on the local heat transfer distribution on smooth flat plate surface impinged with normal air jet. Reynolds number based on nozzle exit condition is varied between 1000 and 4000 and heat flux from 500 to 1000 W/m2. The flow domain was studied by solving Navier Stokes equations by finite volume while the conduction in the plate was studied by solving Laplace equation. The results are expressed in terms of flow field and isotherm contours. The temperature of the plate surface increases when heat flux increases. The thickness of the thermal boundary layer and plate surface temperature decreases when Reynolds number increases.